The mirror illusion: does proprioceptive drift go hand in hand with sense of agency? - Tajima, Daisuke; Mizuno, Tota; Kume, Yuichiro; Yoshida, Takako (Frontiers in Psychology, 2015)
Vection can be regarded as the illusion of ‘whole-body’ position perception. In contrast, the mirror illusion is that of ‘body-part’ position perception. When participants viewed their left hands in a mirror positioned along the midsaggital axis while moving both hands synchronously, they hardly noticed the spatial offset between the hand in the mirror and the obscured real right hand. This illusion encompasses two phenomena: proprioceptive drift and sense of agency. Proprioceptive drift represented a perceptual change in the position of the obscured hand relative to that of the hand in the mirror. Sense of agency referred to the participants’ subjective sense of controlling body image as they would their own bodies. We examined the spatial offset between these two phenomena. Participants responded to a two-alternative forced choice (2AFC) question regarding the subjective position of their right hands and questionnaires regarding sense of agency at various positions of the right hand. We analysed the 2AFC data using a support vector machine and compared its classification result and the questionnaire results. Our data analysis suggested that the two phenomena were observed in concentric space, but the estimated range of the proprioceptive drift was slightly narrower than the range of agency. Although this outcome can be attributed to differences in measurement or analysis, to our knowledge, this is the first report to suggest that proprioceptive drift and sense of agency are concentric and almost overlap.